Rebranding in Action: How Rebranding of Kopi Janji Jiwa Enhances Customer Loyalty in the Jabodetabek Area - Bujana, I Putu Gede; Prayitno, Sentot Basuki (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study highlights the effects of brand attachment, brand distinctiveness, and consumer attitudes on Kopi Janji Jiwa's brand loyalty for Indonesia, resulting in dealing with product rebranding. The paper provides four hypotheses to investigate the direct and indirect effects of brand attachment on brand loyalty as well as the moderating influence of brand distinctiveness based on the Consumer-Brand Relationship theory and the Theory of Planned Behavior.  Data was gathered via a web survey targeted at Kopi Janji Jiwa customers and examined using descriptive and inferential statistics. The findings show that brand loyalty is much enhanced by brand attachment, therefore emphasizing the important part emotional ties play in customer retention during rebranding initiatives. Although consumer attitude does not shield the link between attachment and loyalty, brand distinctiveness has a significant moderating influence; when consumers view the brand as unique, the effect of brand attachment on loyalty is strengthened. The results imply that instead of concentrating just on visual changes, rebranding projects should concentrate on the maintenance and promotion of emotional connections and uniqueness, therefore offering useful guidance for brand managers in the coffee sector as well as others. The study theoretically expands the function of brand distinctiveness as a contextual enhancer of emotional influence and validates the importance of emotional components in consumer-brand relationships, so challenging conventional attitude-based loyalty models and so contributing to branding literature.